The End of the United States Naval Medical Research Unit-2 Project in Indonesia From a Cooperative Security Perspective - Oktaviani, Diva Rahma; Sudirman, Arfin (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The presence of NAMRU-2 in Indonesia has created pros and cons in the community. NAMRU-2, or Naval Medical Research Unit-2, is a United States military medical research unit that operates in various countries, including Indonesia—several pro and con arguments related to its presence in Indonesia in realizing cooperation security. This study aims to investigate NAMRU-2’s role in fostering cooperative health security in Indonesia and examine why the government chose not to renew its cooperation between NAMRU-2 and Indonesia. This study used a qualitative research method with a descriptive approach. The data obtained in this study were obtained from literature studies and interviews. Then, the data validity process is carried out using data triangulation so that the data obtained can provide strong support for the research. The results show that NAMRU-2 in Indonesia does its job well in carrying out the mission of Military Operations Other than War in medical operations. NAMRU-2 successfully dealt with health threats in Indonesia. However, the cooperation of NAMRU-2 in Indonesia failed to realize the security of cooperation. With NAMRU-2 in Indonesia, there is still tension and a lack of trust in the United States government. In addition, the presence of NAMRU-2 made the Indonesian people feel unsafe. After the end of NAMRU-2 in Indonesia, Indonesia has not been independent regarding health security. In this regard, it can be concluded that the existence of NAMRU-2 in Indonesia cannot realize cooperative security because there are still tensions between Indonesia and the United States and the lack of trust of the Indonesian people in the United States. This is not in accordance with the definition of cooperative security.